Hybridity, confucianism, and ambiguity in the South Korean soft power model in Hallyu 1.0 - Loo, Fung Ying; Loo, Fung Chiat (Deepak Ranjan Jena, 2021)
This paper aims to analyze K-drama’s phenomenon as a popular cultural product that generated Hallyu 1.0 and South Korea’s soft power. Past literature suggests this manufactured television drama is a hybrid of ancient Eastern values and Western modernity that resulted in a female-centric and youth consumption. Confucianism and family values are discussed as a backbone of K-drama’s narrative. On the other hand, the “reserved romance” and conservativeness that led to a particular focus on gendering male K-drama actors invited much debate around the new label of “soft masculinity.” However, we question the absence of discussion and detailed analysis of major elements in the Korean popular cultural production that we found are similar to many identical Western models, including the theme song as the catalyst of Hallyu 2.0, “reserved romance,” and ambiguity in the discussion of image branding among male idols, that may not fully reflect claims of Confucianism.